2016
DOI: 10.18632/oncotarget.8522
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody against the Wnt signaling inhibitor dickkopf-1 inhibits osteosarcoma metastasis in a preclinical model

Abstract: The outcome of patients with metastatic osteosarcoma has not improved since the introduction of chemotherapy in the 1970s. Development of therapies targeting the metastatic cascade is a tremendous unmet medical need. The Wnt signaling pathway has been the focus of intense investigation in osteosarcoma because of its role in normal bone development. Although the role of Wnt signaling in the pathogenesis of osteosarcoma is controversial, there are several reports of dickkopf-1 (DKK-1), a Wnt signaling antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 32 publications
0
43
1
Order By: Relevance
“…In support of this, knockdown of DKK1 decreased tumour growth and angiogenesis in hepatocellular carcinoma (Huang et al , ). In addition to affecting primary tumour growth, DKK1 has also been linked to the development of metastasis in bone, breast, liver, lung and prostate cancer models, possibly related to the prominent role of DKK1 in stimulating migration and invasion observed in vitro (Thudi et al , ; Tao et al , ; Huang et al , ; Goldstein et al , ; Malladi et al , ; Pang et al , ). Taken together, these data demonstrate that DKK1 has tumour‐promoting activity in animal models via effects on tumour growth, metastasis and angiogenesis.…”
Section: Dkk1 Promotes Proliferation Invasion and Tumour Growth In Pmentioning
confidence: 99%
“…In support of this, knockdown of DKK1 decreased tumour growth and angiogenesis in hepatocellular carcinoma (Huang et al , ). In addition to affecting primary tumour growth, DKK1 has also been linked to the development of metastasis in bone, breast, liver, lung and prostate cancer models, possibly related to the prominent role of DKK1 in stimulating migration and invasion observed in vitro (Thudi et al , ; Tao et al , ; Huang et al , ; Goldstein et al , ; Malladi et al , ; Pang et al , ). Taken together, these data demonstrate that DKK1 has tumour‐promoting activity in animal models via effects on tumour growth, metastasis and angiogenesis.…”
Section: Dkk1 Promotes Proliferation Invasion and Tumour Growth In Pmentioning
confidence: 99%
“…Mice that were homozygous for the total Dkk1 knockout died at birth due to defects in the cranium and structures formed by the neural crest . Several studies have reported that elevated levels of DKK‐1 were associated with disease severity or a poor prognosis, which provided a rationale to regulate the canonical Wnt pathway in cancer and bone diseases for therapeutic purposes . It has been shown that DKK‐1 might also use cell‐to‐cell contact to bind to LRP‐6 …”
Section: Introductionmentioning
confidence: 99%
“…; see the Supporting information: Image based analysis of immunochemistry slides). Because DKK1 has been demonstrated to be a pathologically essential and strong prognostic factor in several studies, including ours, DKK1 could be a potential candidate for a future preclinical study of anti‐ DKK1 therapy in HCC, as described for myeloma (Fulciniti et al ., ) and osteosarcoma (Goldstein et al ., ).…”
Section: Discussionmentioning
confidence: 97%